2016
DOI: 10.1155/2016/9638041
|View full text |Cite
|
Sign up to set email alerts
|

Early Gastric Cancer: Current Advances of Endoscopic Diagnosis and Treatment

Abstract: Endoscopy is a major method for early gastric cancer screening because of its high detection rate, but its diagnostic accuracy depends heavily on the availability of endoscopic instruments. Many novel endoscopic techniques have been shown to increase the diagnostic yield of early gastric cancer. With the improved detection rate of EGC, the endoscopic treatment has become widespread due to advances in the instruments available and endoscopist's experience. The aim of this review is to summarize frequently-used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…With advances in diagnostic techniques, the rates of detecting early-stage gastric cancer (EGC), defined by the depth of the neoplastic invasion being restricted to the submucosal layer of the stomach, irrespective of lymph node (LN) metastasis, has increased to almost 20% in some countries (1,2). Although early diagnosis affords the opportunity for minimally invasive treatment such as endoscopic resection, this procedure remains only potentially curative as a frontline and unimodal therapy in a subset of EGC patients (1)(2)(3). Furthermore, the current rudimentary classification system of EGC does not quantitatively phenotype patient tumors at the molecular level, and overlooks any degree of metastatic potential, thus raising concerns that therapeutic endoscopy may still yield incorrect prognoses in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in diagnostic techniques, the rates of detecting early-stage gastric cancer (EGC), defined by the depth of the neoplastic invasion being restricted to the submucosal layer of the stomach, irrespective of lymph node (LN) metastasis, has increased to almost 20% in some countries (1,2). Although early diagnosis affords the opportunity for minimally invasive treatment such as endoscopic resection, this procedure remains only potentially curative as a frontline and unimodal therapy in a subset of EGC patients (1)(2)(3). Furthermore, the current rudimentary classification system of EGC does not quantitatively phenotype patient tumors at the molecular level, and overlooks any degree of metastatic potential, thus raising concerns that therapeutic endoscopy may still yield incorrect prognoses in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic ultrasound is available only in select centres. 7 Ultrasonography (USG) and Multidetector Computed Tomography (CT) with Multiplanar Reformation (MPR) gives both physiological as well as anatomical description of the site and extension of lesion within the lumen, as well as beyond the lumen. 4,5 The other modalities which are used are Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET).…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic procedures are used to screen high risk symptomatic patients by detecting morphological changes in gastrointestinal mucosa. Even as a gold standard technique, endoscopic procedures do not allow effective differentiation of neoplastic gastric lesions from healthy or stressed tissue due to their indiscernible microstructural differences [ 40 ]. Nam et al have demonstrated that early detection of GC requires repeated endoscopic procedures owing to the rate of false negatives associated with the procedure [ 41 ].…”
Section: Antibody-fluorescent Dyes For Gc Diagnosismentioning
confidence: 99%